Ambient Intelligence First International Joint Conference, AmI 2010, Málaga, Spain, November 10-12, 2010, Proceedings - De Ruyter, Boris; Wichert, Reiner; Keyson, David V.; Markopoulos, Panos; Streitz, Norbert; Divitini, Monica; Georgantas, Nikolaos; Mana Gomez, Antonio (Information Systems and Applications, incl. Internet/Web, and HCI, 2010)
In a world supported by Ambient Intelligence (AmI), various devices embedded in the environment collectively use the distributed information and the intelligence inherent in this interconnected environment. A range of information from sensing and reas- ing technologies is used by distributed devices in the environment. The cooperation between natural user interfaces and sensor interfaces covers all of a person's s- roundings, resulting in a device environment that behaves intelligently; the term "Ambient Intelligence" has been coined to describe it. In this way, the environment is able to recognize the persons in it, to identify their individual needs, to learn from their behavior, and to act and react in their interest. Since this vision is influenced by a lot of different concepts in information proce- ing and combines multi-disciplinary fields in electrical engineering, computer science, industrial design, user interfaces, and cognitive sciences, considerable research is needed to provide new models of technological innovation within a multi-dimensional society. Thus the AmI vision relies on the large-scale integration of electronics into the environment, enabling the actors, i.e., people and objects, to interact with their surrounding in a seamless, trustworthy, and natural manner.